2000
DOI: 10.1007/s005350070044
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in bilirubin metabolism research: the molecular mechanism of hepatocyte bilirubin transport and its clinical relevance

Abstract: Bilirubin is taken up from blood into hepatocytes by sinosuidal membrane transporters and then excreted into bile through the bile canalicular membrane mainly as bilirubin glucuronides. (1) Mechanism of bilirubin uptake into hepatocytes: many organic anions are incorporated into hepatocytes by organic anion transporting polypeptides (rat, oatp1, oatp2, oatp3; human, OATP), liver-specific transporter (rlst/HLST), and/or by organic anion transporters (OAT2, OAT3). Oatp1 and HLST transport bilirubin monoglucuroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 56 publications
0
86
0
Order By: Relevance
“…Normally, these steps are performed by active transporters in the liver (Kamisako et al, 2000;Thomas et al, 2008). Thus, we evaluated, by semiquantitative RT-PCR, the expression of different transporters known to export conjugated/unconjugated bilirubin from hepatocytes (Fig.…”
Section: Fig 2 Persistence Of Hugt1a1 Transgene Expression In Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, these steps are performed by active transporters in the liver (Kamisako et al, 2000;Thomas et al, 2008). Thus, we evaluated, by semiquantitative RT-PCR, the expression of different transporters known to export conjugated/unconjugated bilirubin from hepatocytes (Fig.…”
Section: Fig 2 Persistence Of Hugt1a1 Transgene Expression In Livermentioning
confidence: 99%
“…This striking difference in the therapeutic effect between liver and skeletal muscle apparently resides in the liverspecific expression of Mrp2 and/or Mrp3 transporters (also known as Abcc2 and Abcc3, respectively), which extrude conjugated bilirubin from the hepatocyte to the bile and blood, respectively (Kamisako et al, 2000). Taken together, our data strongly support the concept that the liver is the most suitable target organ for efficient CNSI gene therapy and suggest that the potential use of extrahepatic tissues should be directly related to the presence of bilirubin transporters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their excellent biocompatibility and chemical/mechanical stability allow them to adsorb toxic pathogenic substances in vivo. We demonstrated that HMCNs could act as a clinical adsorbent for bilirubin [90], which can cause crippling, athetoid cerebral palsy and even death if overproduced [91]. Various absorbents such as activated carbon, chitosan, resins, and porous TiO 2 have been employed as adsorption materials in hemoperfusion columns to remove bilirubin from the blood [90].…”
Section: Reviewsmentioning
confidence: 99%
“…[6] Levels of bilirubin in blood are normally below 1.0 mg/dL (17 51 µmol/L) typically results in jaundice. [7][4] High bilirubin is divided into two types: unconjugated (indirect) and conjugated (direct). [8] Conjugated bilirubin can be confirmed by finding bilirubin in the urine.…”
mentioning
confidence: 99%
“…[10] Among newborns, depending on age and prematurity, a bilirubin greater than 4-360 µmol/L) may be treated with phototherapy or exchanged transfusion. [7] The itchiness may be helped by draining the gallbladder or ursodeoxycholic acid. [3] The word jaundice is from the French jaunisse, meaning "yellow…”
mentioning
confidence: 99%